An Efficient Method for the Synthesis of Boratrane Complexes of Late Transition Metals. Issue 72 (30th November 2017) - Saha, Koushik; Ramalakshmi, Rongala; Borthakur, Rosmita; Gomosta, Suman; Pathak, Kriti; Dorcet, Vincent; Roisnel, Thierry; Halet, Jean‐François; Ghosh, Sundargopal
Abstract: In a quest for efficient precursors for the synthesis of boratrane complexes of late transition metals, we have developed a useful synthetic method using [L′M(μ‐Cl)Cl x ]2 as precursors (L′=η 6 ‐ p ‐cymene, M=Ru, x= 1; L′=COD, M=Rh, x= 0 and L′=Cp*, M=Ir or Rh, x= 1; COD=1, 5‐cyclooctadiene, Cp*=η 5 ‐C5 Me5 ). For example, treatment of Na[(H3 B)bbza] or Na[(H2 B)mp2 ] (bbza=bis(benzothiazol‐2‐yl)amine; mp=2‐mercaptopyridyl) with [L′M(μ‐Cl)Cl x ]2 yielded [(η 6 ‐ p ‐cymene)RuBH{(NCSC6 H4 )(NR)}2 ] (2 ; R=NCSC6 H4 ), [{N(NCSC6 H4 )2 }RhBH{(NCSC6 H4 )(NR)}2 ] (3 ; R=NCS‐C6 H4 ), [(η 6 ‐ p ‐cymene)RuBH(L)2 ] (5 ; L=C5 H4 NS), and [Cp*MBH(L)2 ] (6 and7 ; L=C5 H4 NS, M=Ir or Rh). In order to delineate the significance of the ligands, we studied the reactivity of [(COD)Rh(μ‐Cl)]2 with Na[(H3 B)bbza], which led to the formation of the isomeric agostic complexes [(η 4 ‐COD)Rh(μ‐H)BHRh(C14 H8 N3 S2 )3 ], 4 a and4 b, in parallel to the formation of 16‐electron square‐pyramidal rhodaboratrane complex3 . Compounds4 a and4 b show two different geometries, in which the Rh−B bonds are shorter than in the reported Rh agostic complexes. The new compounds have been characterized in solution by various spectroscopic analyses, and their structural arrangements have been unequivocally established by crystallographic analyses. DFT calculations provide useful insights regarding the stability of these metallaboratrane complexes as well as their M→B bonding interactions. Abstract : Rare M→B bonding : Members of a series of 16‐ and 18‐electron Group 8 and 9 metallaboratrane complexes featuring M→B dative bonds (see graphic) have been prepared using different metal precursors, such as [( p ‐cymene)RuCl2 ]2 and [(COD)Rh(μ‐Cl)]2, and borate ligands.